Sperm allocation strategies in a sperm heteromorphic insect. Issue 3 (11th October 2019) - Esfandi, Kambiz; He, Xiong Z; Wang, Qiao
Abstract: Theories predict that in polyandrous species, the focal male should increase sperm allocation per mate in the presence of rivals to gain greater share of paternity, but in the presence of additional mates, he should reduce sperm allocation per mate to save sperm for insemination of more mates. However, empirical findings are often inconsistent and reasons behind are unclear. Furthermore, many studies use copulation duration as an estimate of the number of sperm transferred. Yet, empirical evidence for such assumption is largely lacking. Here, we used a sperm heteromorphic insect Ephestia kuehniella whose males produce two types of sperm, eupyrenes (fertile) and apyrenes (nonfertile), to test these postulations. We allowed focal males to detect chemical and acoustic but no tactile cues from rivals or additional mates both before and during mating and measured copulation duration and sperm allocation in successive copulations. We demonstrate that males transfer significantly more eupyrenes per mate in the presence of rivals and that the sperm allocation pattern persists in successive copulations under this condition. However, males do not adjust apyrene allocation in response to rivals probably because apyrenes play a relatively minor role in male reproductive success. Contrary to a previous study, focal males do not respond to additional mates most likely due to the lack of tactile cues in the present study. We reveal that sperm allocation is not a function of copulation duration in this insect for spermatophore formation and delivery occupy most of copulation duration and sperm transfer is complete near the end of copulation.